ERS International Congress 2022: highlights from the Interstitial Lung Diseases Assembly - Karampitsakos, Theodoros; Diep, Phuong Phuong; Loth, Daan W.; Nadeem, Iftikhar; Khurtsidze, Elene; Wijsenbeek, Marlies S.; Wuyts, Wim A.; Bargagli, Elena; Froidure, Antoine; Spagnolo, Paolo; Veltkamp, Marcel; Molina-Molina, Maria; et al. (ERJ Open Research, 2023)
This article contains a selection of scientific highlights in the field of interstitial lung diseases (ILDs) presented at the hybrid European Respiratory Society International Congress 2022. Early Career Members of Assembly 12 summarise recent advances in translational and clinical research in idiopathic interstitial pneumonias, ILDs of known origin, sarcoidosis and other granulomatous diseases, and rare ILDs. Many studies focused on evaluation of diagnostic and prognostic (bio)markers, and novel pharmacological and nonpharmacological treatment options for different ILDs. In addition, new insights in clinical, physiological and radiological features of various rare ILDs were presented. - Tweetable abstract ERSpublications - click to tweetEarly Career Members of @ers_ild summarise recent advances in translational and clinical research in idiopathic interstitial pneumonias, ILDs of known origin, sarcoidosis and rare ILDs presented at #ERSCongress 2022 https://bit.ly/3hcvqFf
Gesehen am 15.06.2023